(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
What are the determinations that can guide our research to analyze the advance of the extreme right in the world? To this end, the proposed question considers the relationship between technology and politics, and aims to analyze the Global Technopolitical Network of the Far Right. The proposed challenge is to unveil the different articulations that define the formation of the technopolitical network. Its objective is to identify its agents, examine the division of labor, analyze its articulations and the narratives that circulate within it, to demonstrate that its communication vectors produce a collective subjectivity of the extreme right. We highlight the participation of the influence industry which, through its algorithms, produces data analysis capable of recognizing target social groups, which identify themselves by their way of thinking, doing and being shared. To whom fake news is directed, which produces a “parallel reality” and “cognitive dissonance”. It transforms power relations in the world to benefit authoritarian and conservative values. The methodology’s starting point is interdisciplinarity, which combines knowledge of political science, communication, computing and geography. The data collection focuses on the action structure of the global far-right network and its representation in Brazil. The procedures are supported by a database that documents the information and application of computer programs to represent the networks. The analytical results identify the actors and agents, examine the division of labor in the technopolitical network to analyze their narratives, the processes and strategies of right-wing power, and demonstrate the expansion of political participation beyond political parties. No less important is revealing the connections between the global extreme right and the extreme right in Brazil and their consequences for democracy in the world.